Optimalisasi Sistem Pengairan pada Tanaman Obat Keluarga (TOGA) melalui Irigasi Sprinkler di Desa Gempol Nganjuk - Maulana, Hendra; Karina, Febrian Agung Dwi; Pratiwi, Iramandha Putri; Sugiarto, Mercy Aulia; Maulana, M. Abizzar (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
Gempol Village, Rejoso District, Nganjuk Regency, is a village with most of its population working as farmers. The factor that encourages residents of Gempol Village to work as farmers is that most of the area is still agricultural land and the other regions are used as residential areas for the population of Gempol Village with a total of 1,962 people. So the impact of low population density is that there is a lot of empty land that is still not being utilized optimally. Therefore, researchers see an opportunity for empty land to be used as a TOGA Park. The research methods used are observation, design of the main construction of Sprinkler irrigation, and design of Sprinkler irrigation systems. TOGA Park in Gempol Village requires regular watering, so the Sprinkler irrigation system was chosen because it can increase efficiency and effectiveness in meeting TOGA's water needs. Apart from that, the Sprinkler irrigation system in TOGA Park also needs attention in its maintenance to increase efficiency and effectiveness in meeting TOGA's water needs. Keywords: TOGA, Irrigation System, and Sprinkler